Hubungan Bilateral Indonesia-Malaysia dalam Persoalan TKI Ilegal Tahun 2004-2011 - Martin Rizaldi; Anin Lailatul Qodariyah (CHRONOLOGIA, 2021)
This article aims to find out about international relations in the bilateral cooperation between Indonesia and Malaysia in the problem of illegal TKI. The method of preparing this article uses the literature review method, the literature review method is a research method that uses reference sources from books and journals. The problem of illegal TKI cannot be separated from the problems that are often faced in Indonesia, namely the problem of unemployment and the problem of limited employment opportunities. There are several factors that encourage Indonesians to work as migrant workers in Malaysia. To resolve the TKI problem, the respective governments of Indonesia and Malaysia carry out bilateral cooperation which aims to create a prosperous life for the nation and state together. Keywords: Indonesia, Malaysia, TKI. Abstrak Artikel ini bertujuan untuk mengetahui hubungan internasional pada kerjasama bilateral Indonesia-Malaysia dalam Persoalan TKI ilegal. Metode penyusunan artikel ini menggunakan metode kajian pustaka, metode kajian pustaka adalah metode penelitian yang menggunakan sumber referensi dari buku dan jurnal. Persoalan TKI ilegal tidak terlepas dari masalah yang sering dihadapi di Indonesia yaitu masalah pengangguran dan masalah terbatasnya lapangan pekerjaan. Ada beberapa faktor yang mendorong orang Indonesia untuk bekerja sebagai TKI di Malaysia. Untuk menyelesaikan persoalan TKI tersebut, maka masing-masing pemerintah dari negara Indonesia dan Malaysia melakukan kerjasama bilateral yang bertujuan untuk menciptakan kesejahteraan kehidupan berbangsa dan bernegara secara bersama. Kata Kunci : Indonesia, Malaysia, TKI.